2019
DOI: 10.1002/ana.25440
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and small vessel stroke: A mendelian randomization analysis

Abstract: Objective Trials of B vitamin therapy to lower blood total homocysteine (tHcy) levels for prevention of stroke are inconclusive. Secondary analyses of trial data and epidemiological studies suggest that tHcy levels may be particularly associated with small vessel stroke (SVS). We assessed whether circulating tHcy and B vitamin levels are selectively associated with SVS, but not other stroke subtypes, using Mendelian randomization. Methods We used summary statistics data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 53 publications
4
52
0
3
Order By: Relevance
“…Obvious platelet aggregation may be secondary to the direct promoting effect of homocysteine or the inhibition of platelets mediated by the endothelium 15, . Some studies have found that folic acid, vitamin B6 and vitamin B12 can reduce the level of homocysteine, thus reducing small vessel stroke, which is consistent with the ndings of the children in this study 17 . Therefore, for children with basal ganglia ischaemic stroke, the level of homocysteine should be routinely screened and followed up.…”
Section: Discussionsupporting
confidence: 92%
“…Obvious platelet aggregation may be secondary to the direct promoting effect of homocysteine or the inhibition of platelets mediated by the endothelium 15, . Some studies have found that folic acid, vitamin B6 and vitamin B12 can reduce the level of homocysteine, thus reducing small vessel stroke, which is consistent with the ndings of the children in this study 17 . Therefore, for children with basal ganglia ischaemic stroke, the level of homocysteine should be routinely screened and followed up.…”
Section: Discussionsupporting
confidence: 92%
“…A recent Mendelian randomization analysis and the Vitamins to Prevent Stroke (VITATOPS) trial both found that lowering of homocysteine is associated with only the small vessel subtype of ischemic stroke-which accounts for 37.7% of ischemic and 27.9% of overall stroke in Taiwan 2 -but not other subtypes (large artery or cardioembolic). 41,45 The ICD-9-CM code could not distinguish to such detail and our studies would not have enough power to examine these detailed subtypes of ischemic stroke. In our study, the percentage of study participants with hyperhomocysteinemia (defined as >20 μmol/L) is low (2% in nonvegetarians vs 5% in vegetarians), likely due to healthy overall lifestyle (nonsmoking, no alcohol drinking, adequate folate intake through high vegetable consumption), thus stroke risk attributable to hyperhomocysteinemia is probably low.…”
Section: Discussionmentioning
confidence: 95%
“…8,40 Previous cohort studies found that the highest vs lowest adherence to DASH and Mediterranean diet were associated with a 10%-20% reduction in hemorrhagic stroke. 12,14,41 In addition to the BP-lowering effect common to most plant-based diets, a vegetarian diet may have the additional advantage of reduced TMAO, 35 and TMAO has been positively associated with hemorrhagic stroke risk among hypertensive individuals in a recent nested casecontrol study. 34 Many studies reporting inverse associations between intake of animal products and hemorrhagic stroke focus on a single food or nutrient.…”
Section: Discussionmentioning
confidence: 99%
“…: hyperlipidaemia, renal and hepatic insufficiency) and medications (metformin, fenofibrate, thiazide diuretics) [21]. Nonetheless, a mendelian randomisation analysis of European-descent ischaemic stroke patients found that genetically higher blood Hcy levels are associated with SVD related stroke, but not with large artery stroke or cardioembolic stroke [22].…”
Section: Discussionmentioning
confidence: 99%